AN INTRODUCTION TO EAST AFRICAN MUSIC FOR SCHOOLS by S. Mbabi-Katana. Milton Obote Foundation. Kampala, Uganda. - Gourlay, Ken A. (International Library of African Music, 1970)
pages: 128-130
Keywords: African Music; Uganda